Broadband Dual-Polarized Multidipole Antenna for Base Station Applications. (10th September 2021) - Huang, Yuxuan; Zhu, Zeqi; Cai, Shuting; Xiong, Xiaoming; Liu, Yuan
Abstract : A wideband dual-polarized multidipole antenna for base station applications is proposed. It consists of a pair of large square-shaped loop dipoles and a pair of small rectangle loop dipoles as radiation elements. A pair of small rectangle loop dipoles is fed by T-shaped feed structure which is in the large square-shaped loop dipoles radiating arm so that the antenna generates an additional resonance and obtains a wider bandwidth. The proposed antenna was fabricated and measured, and the results show that the antenna achieves a wide impedance bandwidth of 63.7 % with VSWR<1.5 covering the frequency range from 1.55 to 3 GHz. A high isolation is better than 29 dB within the operating frequency bandwidth. Moreover, an average gain 8 dBi and a stable radiation pattern with 3 dB beamwidth of 69° ± 4° at H-plane are obtained.